Features Of The Anamnestic And Hormonal Background Of Women With Abnormal Uterine Bleeding Associated With Adenomyosis - Gulistan Bekbaulieva (International Journal of Medical Sciences And Clinical Research, 2025)
In the FIGO PALM-COEIN classification system, adenomyosis is considered one of the nosology’s causing abnormal uterine bleeding (AUB). AUB associated with adenomyosis not only worsens the quality of life for women of reproductive age but also causes significant economic damage to the state. Adenomyosis remains one of the enigmatic pathologies in modern gynecology, from pathogenesis and diagnosis to treatment. Therefore, we aimed to study the features of the anamnestic and hormonal backgrounds in patients with AUB due to adenomyosis. To achieve this goal, women were divided into two groups: Group I (main group, women with AUB associated with adenomyosis) included 160 women aged 28–49 years, and Group II (control group) included 132 women aged 28–49 years without AUB or adenomyosis. The results showed that the medical history of patients with AUB due to adenomyosis was burdened with infertility, miscarriage, and fibrocystic mastopathy in the majority of women, indicating hormonal imbalance in this pathology. The hormonal profile of patients with AUB due to adenomyosis revealed a significant increase in mean serum testosterone levels (3.6 ± 0.12 nmol/L vs. 1.68 ± 0.05 nmol/L in the control group, (P < 0.001 \)). Additionally, hormonal imbalances were identified: hyperestrogenemia in 71.3 ± 1.4% of cases, hypoprogesteronemia in 31.7 ± 3.9%, and thyroid hypofunction in 41.3 ± 1.9%.